Forecasting of development of acute poisonings in agricultural workers while using combined formulations based on difenoconazole. - P. V. Stavnichenko; A. M. Antonenko; V. G. Bardov (Medičnì Perspektivi)
In the general structure of occupational diseases, a large proportion belongs to acute poisoning with pesticides (mainly group cases). However, today it is impossible to drop the use of pesticides in agriculture. Their application ensures high biological and economic efficiency of the latter, reduces losses of the yield. The purpose of the work was to predict the possibility of acute toxic effects in agricultural workers when working with combined formulations based on difenoconazole. Materials and methods. To assess the influence on the organism of the workers of the above-mentioned substances and formulations on their basis, the coefficient of inhalation poisoning possibility (CIPP), the coefficient of selective action of the pesticide in inhalation effect (CSAing) and the selective action of the pesticide in the dermal effect (CSAderm) were calculated. Results. Calculated values of CSAing (103.4-4701.2) and CSAderm (237.4-12345.7) for all investigated active substances were more than 100, this indicates to a rather high selectivity of their action. By the CSAing value formulations Celeste Top, Celeste Trio, Dinali, Cydeli Top belong to pesticides with a relatively low selectivity of action when they are inhaled by workers in the process of crops treating, the remaining formulations have a sufficient selectivity of action in inhalation intake. In addition, it should be noted that in general, for all combined preparations CSA values are significantly lower than for separateactive ingredients, in addition to the above assumption, can be explained by the presence of other formulants in the preparation that may have not significant but toxic effect on the body of workers. All investigated substances in the probability of occurrence of acute poisoning with the use of combined preparations on their basis are related to the 4th grade of danger according to State Standards 8.8.1.002-98. There was proved relative safety in case of penetration into the organism of agricultural workers by percutaneous and inhalational way of all studied active ingredients and most of the formulations on their basis.